PENGEMBANGAN LABORATORIUM VIRTUAL PADA MATERI LARUTANELEKTROLIT DAN NON-ELEKTORLIT - Khaeruman, Khaeruman; Khery, Yusran; Murdiono, Murdiono (Jurnal Ilmiah IKIP Mataram, 2018)
Less laboratory facilities was become major constraint in most of public or private school in Lombok. Some of school was not have laboratory or laboratory equipment. Therefore, virtual laboratory was developed on this research.The aim of this research was to evaluate eligibility of virtual laboratory learning media in electrolyte and non-electrolyte solution media. 4D model limited on define, design, and development step was carried out on this research and development. Eligibility test was executed by expert (IKIP Mataram Lecturer) validation and student assessment on limited group trial in SMA Islam Al Azhar NW Kayangan Lombok Barat. Development result showed that developed virtual laboratory learning media was eligible for application on learning process. It was concluded from 88.53 % of average eligibility percentage by expert validation result and 91 % by 10 students on limited trial.